Crítica y política desde el Arte gráfico de caricatura: reseña al libro YO Alan de Carlos Tovar, Carlín - Díaz Aparicio, Ademar (2019)
At the beginning of the 1980s, several notability of Peruvian graphic art, such as Carlos Tovar, Carlos Acevedo, Eduardo Rodríguez and others, made the figure of Alan García the face of the birth of a new Peruvian class based on criollismo, liveliness and the excessive bribery. This apparent impudence implicit in the graphics about the person of the president and the issues that covered his personal imprints as a key figure of transition from the oligarchy to choledad (Nugent, 1990) are extraordinarily exposed in Yo Alan, a book by the engineer and cartoonist Carlos Tovar , known in the media as Carlin, which was edited by the publisher Grafal in 1990.